Communicable Disease Patterns and Public Health Policy Responses: A SWOT Analysis in an Island Region - M. Fais Satrianegara; Nildawati Nildawati; Syamsul Alam (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Communicable diseases pose a major threat to public health with significant impacts on mortality rates. Despite efforts to control these diseases, challenges in addressing their spread remain, especially in regions with limited resources. Kabupaten Pangkajene and Kepulauan faces this issue, with diseases such as ISPA, Diarrhea, and Tuberculosis (TBC) being the main concerns. Objective: This study aims to analyze the trends in the spread of communicable diseases and evaluate the health policies implemented in Kabupaten Pangkajene and Kepulauan from 2021 to 2023. Methods: This research adopts a mixed-methods approach. The quantitative approach analyzes disease trends based on case report data from the Health Office and Public Health Centers (Puskesmas). The qualitative approach involves Focus Group Discussions (FGD) and interviews with program implementers to evaluate health policies. SWOT analysis is used to identify the strengths, weaknesses, opportunities, and threats related to disease prevention policies. Results: ISPA, Diarrhea, and Tuberculosis (TBC) are the main communicable diseases in Kabupaten Pangkajene and Kepulauan from 2021 to 2023. The SWOT analysis reveals strengths in community awareness but weaknesses in healthcare infrastructure. Opportunities to strengthen the health system are abundant, while threats from disease spread and resource shortages remain significant. Conclusion: Communicable diseases are rising in Pangkajene and Kepulauan Regency, notably respiratory infections, diarrhea, and tuberculosis. The SWOT analysis reveals both systemic strengths and areas for policy intervention. Strengthening public health education, healthcare infrastructure, disease surveillance, and GIS-based risk mapping is essential. These findings offer critical insights for policymakers to redesign regional health strategies, allocate resources more effectively, and build a resilient, data-driven response framework for managing current and future public health threats.